Cross-linked antistatic supercritical microcellular foaming material as well as preparation method and application thereof
By adding specific raw materials to the HIPS matrix and building a multiple cross-linking network, the shortcomings of HIPS materials in supercritical micropore foaming and anti-static properties are solved, and high-performance cross-linked anti-static supercritical micropore foaming materials are realized. , suitable for multi-field applications.
Patent Information
- Application Number
- CN202411138316.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult for the prior art to directly use high impact polystyrene (HIPS) materials for supercritical microporous foaming, and traditional HIPS materials lack antistatic properties and are difficult to apply in electronic product outer packaging.
Develop a crosslinked antistatic supercritical microporous foaming material by adding organic multifunctional masterbatch, highly dispersed conductive filler, modified calcium sulfate whiskers and grafted modified talc powder masterbatch to the HIPS matrix, and Multiple crosslinking networks are constructed using crosslinking agents to improve the antistatic and mechanical properties of the materials.
It has achieved stable and excellent comprehensive performance anti-static HIPS supercritical microporous foaming material, with excellent anti-static properties and comprehensive mechanical properties, and is suitable for electronic product outer packaging and other applications in many fields.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a cross-linked antistatic supercritical microporous foaming material and a preparation method and application thereof. Background Art
[0002] Supercritical fluid microporous foaming technology is a green and environmentally friendly production and processing method that has emerged in recent years. Compared with traditional chemical foaming technology, it not only does not leave harmful chemical substances, but can also be used for auxiliary processing, promote the plasticization of polymer materials, and improve the matrix toughness and impact strength of materials. Therefore, using supercritical fluid as a foaming agent for polymer materials is an epoch-making engineering technology.
[0003] Different from gases such as chlorofluorocarbons and alkanes used in traditional physical foaming, supercritical fluids do not have the environmental pollution or flammable and explosive environmental safety issues caused by the use of such gases. Supercritical fluids completely use the supercritical state of clean gases and will not cause secondary pollution to the environment.
[0004] However, the use of supercritical fluid microporous foaming technology has other special requirements for the properties of the polymer material itself. If the melt strength and viscosity of the material are low, the pore structure of the material will deteriorate after supercritical microporous foaming. Therefore, technical improvements are needed to the melt strength and basic properties of the material.
[0005] At present, the market share of polymer materials produced by supercritical fluid microporous foaming technology is not particularly large. The main reason is that there are certain differences in the compatibility between materials and processes. Therefore, obtaining modified materials that are more suitable for supercritical fluid microporous foaming is an important part of obtaining supercritical fluid microporous foaming materials.
[0006] As a traditional foaming material, polystyrene (PS) has a high market share, but traditional foamed PS is mostly beaded kettle foaming, which cannot be continuously produced, and has a high foaming ratio. It is mostly used for thermal insulation materials or buffer materials, and does not have good mechanical properties. Using high-impact polystyrene (HIPS) to produce microporous foam materials can not only avoid the problem of poor material performance caused by foamed PS, but also expand the application field of PS.
[0007] HIPS, as a modified material of PS, has excellent comprehensive properties and better impact strength than PS, and is widely used in white appliances and packaging fields.
[0008] However, although HIPS material has good comprehensive performance, it is currently difficult to directly apply it to supercritical microporous foaming. On the one hand, it is difficult to obtain stable and controllable microporous foaming materials due to its poor melt strength, which easily causes the performance of the material to deteriorate after microporous foaming; on the other hand, the outer packaging of electronic products requires higher antistatic properties, and traditional HIPS itself is an insulating material, which is easy to cause static electricity accumulation and damage electronic products and electronic components, making it difficult to use in electronic products.
[0009] Therefore, in order to break through the limitations of material application, the preparation of HIPS supercritical microporous foaming materials with antistatic properties is a milestone research. Therefore, the development of stable and comprehensive antistatic HIPS supercritical microporous foaming materials is a technical problem that needs to be solved urgently in the current HIPS industry and packaging field.
[0010] At present, there are related patents involving the development of some related materials. For example, the invention patent CN111961305B uses azodicarbonamide as a foaming agent to prepare a microporous HIPS electromagnetic shielding material. The chemical foaming agent used in the invention will remain inside the material and affect the use of the material; the invention patent CN113444363B discloses a TPE supercritical microporous foam and its preparation method. The material involved in the invention can only be formed by autoclave pressing after vulcanization, and is only for rubber systems similar to TPE, and it is difficult to achieve continuous production in PS plastics; the invention patent CN115058044A provides a method for making an antistatic HIPS material. The antistatic property is achieved by coating a layer of polyurethane coating on the outer layer of HIPS, which cannot be maintained for long-term use. In addition, there are some patents and public documents involving the preparation of HIPS or supercritical microporous foam materials, but there is no clear report on cross-linked antistatic HIPS supercritical microporous foam materials. Summary of the invention
[0011] The purpose of the present invention is to overcome the above problems existing in the prior art, provide a cross-linked antistatic supercritical microporous foam material and a preparation method and application thereof, and prepare a cross-linked antistatic HIPS supercritical microporous foam material with excellent comprehensive performance and applicable to multiple fields.
[0012] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0013] In a first aspect, the present invention provides a cross-linked antistatic supercritical microporous foam material, comprising the following raw materials in parts by weight: 80-100 parts of HIPS, 10-15 parts of thermoplastic elastomer, 5-10 parts of low-density polyethylene, 10-15 parts of organic multifunctional masterbatch, 5-10 parts of highly dispersed conductive functional filler, 5-10 parts of modified calcium sulfate whisker, 5-10 parts of grafted modified talc masterbatch, 1-5 parts of cross-linking agent, 1-5 parts of lubricant, and 1-5 parts of antioxidant;
[0014] The organic multifunctional masterbatch comprises the following raw materials in parts by weight: 60-90 parts of SEBS-g-MAH, 10-20 parts of ionic liquid containing active groups, 1-5 parts of nano zinc oxide, and 1-5 parts of erucic acid amide;
[0015] The highly dispersed conductive functional filler comprises the following raw materials in parts by weight: 80-100 parts of conductive functional filler, 5-10 parts of coupling agent, and 1-5 parts of maleic anhydride grafted polyethylene wax;
[0016] The modified calcium sulfate whisker comprises the following raw materials in parts by weight: 90-100 parts of calcium sulfate whisker, 0.5-2 parts of coupling agent II, and 0.3-1 parts of ionic liquid modifier;
[0017] The grafted modified talc masterbatch comprises the following raw materials in parts by weight: 40-50 parts of activated ultrafine talc, 5-20 parts of a silane crosslinking agent containing an active group, 0.1-1 parts of an initiator, 1-2 parts of styrene, and 40-60 parts of high-impact polystyrene.
[0018] Furthermore, the thermoplastic elastomer is a styrene rubber elastomer.
[0019] Furthermore, the preparation method of the organic multifunctional masterbatch comprises the following steps:
[0020] According to the raw material formula of organic multifunctional masterbatch, SEBS-g-MAH, ionic liquid containing active groups, nano zinc oxide and erucic acid amide are weighed, and the weighed SEBS-g-MAH, ionic liquid containing active groups, nano zinc oxide and erucic acid amide are fully mixed by reactive melt blending method, and placed in a twin-screw extruder for melt blending, extrusion and granulation. During the melt blending, extrusion and granulation process, the feeding section temperature of the twin-screw extruder is 120° C.-160° C., the conveying section temperature is 130° C.-160° C., the mixing section temperature is 150° C.-170° C., the exhaust section temperature is 150° C.-165° C., and the homogenization section temperature is 160° C.-180° C. After the melt blending, extrusion and granulation are completed, the organic multifunctional masterbatch is obtained;
[0021] The grafting rate of the SEBS-g-MAH is 1.4%-2.0%, the Shore A hardness is 52-95, and the melt flow rate is 13.0 g / 10min-25.0 g / 10min under the test conditions of a temperature of 230° C. and a load of 5 kg;
[0022] The erucic acid amide is a high molecular weight erucic acid amide, the high molecular weight erucic acid amide acid value is ≤0.9mg KOH / g, the total amide content is ≥95%, and the moisture content is <0.5%;
[0023] Furthermore, the ionic liquid containing active groups is any one or more of ionic liquids containing sulfonic acid groups, ionic liquids containing vinyl groups, ionic liquids containing carboxyl groups, ionic liquids containing hydroxyl groups, ionic liquids containing amino groups or ionic liquids containing epoxy groups, mixed in any proportion.
[0024] Furthermore, the preparation method of the highly dispersed conductive functional filler comprises the following steps:
[0025] According to the raw material formula of highly dispersed conductive functional filler, conductive functional filler, coupling agent 1 and maleic anhydride grafted polyethylene wax are weighed, and a dry surface modification process is adopted to first add the weighed conductive functional filler and coupling agent 1 to a high-speed mixer with an initial temperature of 30-60°C, keep the mixture at 30-60°C for 15-30 minutes, and then mix and stir at high speed for 1-1.5 hours to obtain a conductive functional filler activated and modified by the coupling agent, and then put the weighed maleic anhydride grafted polyethylene wax into the high-speed mixer, and then heat the high-speed mixer to 100-120°C, keep the mixture at high temperature for 15-30 minutes, and then mix and stir for 30-45 minutes to obtain a highly dispersed conductive functional filler;
[0026] The maleic anhydride grafted polyethylene wax has a melting point of 120°C-140°C and a viscosity of 200-400 mPa·s at 140°C.
[0027] Furthermore, the conductive functional filler is any one or more of conductive carbon black, multi-walled carbon nanotubes, graphene, carbon fiber powder, silver metal powder, copper metal powder, and nickel metal powder mixed in any proportion;
[0028] The conductive functional filler has a DBP absorption value of 100-200cc / 100g, an average particle size of 20-50nm, and a surface area of 50-200m 2 / g, resistivity ≤3.5Ω·m;
[0029] The coupling agent 1 and the coupling agent 2 are independently selected from any one or more of silane coupling agents, titanate coupling agents, and aluminate coupling agents and mixed in any proportion;
[0030] The purity of the coupling agent 1 and the coupling agent 2 are both ≥97%, and the decomposition temperature is both ≥260°C.
[0031] Furthermore, the preparation method of the modified calcium sulfate whisker comprises the following steps:
[0032] According to the raw material formula of modified calcium sulfate whiskers, calcium sulfate whiskers, coupling agent II and ionic liquid modifier are weighed, the weighed calcium sulfate whiskers and coupling agent II are placed in a high-speed mixer and stirred evenly, the temperature is raised to 50-70° C. and kept warm for 15-30 minutes, and then mixed and stirred at high speed at 50-70° C. for 1-1.5 hours to obtain calcium sulfate whiskers activated and modified by the coupling agent, and the weighed ionic liquid modifier is added to the calcium sulfate whiskers activated and modified by the coupling agent, and high-speed mixing is continued at 50-70° C. for 1-2 hours to obtain activated modified calcium sulfate whiskers modified by the ionic liquid;
[0033] The calcium sulfate whisker is anhydrous calcium sulfate whisker, with a CaSO4 content of ≥98%, a whiteness of ≥92%, and a loose density of 0.1-0.4g / cm 3 , average diameter is 1-4 μm, average length is 50-200 μm;
[0034] The ionic liquid modifier is any one or more of a carboxyl-containing ionic liquid, a hydroxyl-containing ionic liquid, an amino-containing ionic liquid, a vinyl-containing ionic liquid, an ester-containing ionic liquid, and an ether-containing ionic liquid, mixed in any proportion.
[0035] Furthermore, the preparation method of the grafted modified talc masterbatch comprises the following steps:
[0036] S101: according to the formula, weigh activated ultrafine talc powder, silane crosslinking agent containing active groups, initiator, styrene, and high impact polystyrene;
[0037] S102: adding the weighed silane crosslinking agent containing active groups, initiator, and styrene into a sealed container at room temperature and stirring for 15-30 minutes, and mixing them thoroughly to prepare a composite initiator crosslinking agent;
[0038] Wherein, the purity of styrene is ≥99%;
[0039] S103: adding the weighed high-impact polystyrene and activated ultrafine talc powder into a high-speed mixer, mixing them at a temperature of 30-50° C. and a rotation speed of 3000-4000 r / min, and stopping the mixing until the surface of the high-impact polystyrene is softened and the activated ultrafine talc powder is evenly coated on the surface of the high-impact polystyrene, adding the mixed high-impact polystyrene and activated ultrafine talc powder into an internal mixer at a temperature of 150-190° C., mixing and internal mixing, and then extruding and granulating to prepare granulated particles;
[0040] The high-impact polystyrene is a rubber copolymer-modified polystyrene, and its melt mass flow rate is 3g / 10min-5g / 10min under the test conditions of temperature 200°C and load weight 5kg, the notched impact strength at room temperature is 10-12kJ / m2, the flexural modulus is ≥2150MPa, the tensile strength is ≥25MPa, and the elongation at break is ≥55%;
[0041] The ultrafine talcum powder has a whiteness of ≥90%, a SiO2 content of ≥58%, an average particle size of 1-10 μm, and a volume density of 0.11-0.13 g / cm 3 ;
[0042] S104: adding the granulated particles and the composite initiator crosslinking agent to a high-speed mixer, fully mixing them at room temperature and a rotation speed of 1000-2000r / min to obtain a mixture, and adding the mixture to a twin-screw extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw extruder is 140-180°C, the conveying section temperature is 150-190°C, the mixing section temperature is 180-220°C, the exhaust section temperature is 170-195°C, and the homogenization section temperature is 160-190°C. During the reactive blending process, the melt pressure needs to be controlled to be maintained at 7-10MPa. After the reactive melt blending is completed, the mixture is granulated by water cooling at 30-50°C to obtain a grafted modified talc masterbatch.
[0043] Furthermore, the active groups in the active group-containing silane crosslinking agent are any one or more of vinyl, carboxyl, hydroxyl, epoxy, and amino groups mixed in any proportion;
[0044] The initiator is a peroxide initiator.
[0045] In a second aspect, the present invention provides a method for preparing a cross-linked antistatic supercritical microporous foam material, characterized in that the preparation method comprises the following steps:
[0046] S1: According to the formula of the cross-linked antistatic supercritical microporous foaming material, HIPS, thermoplastic elastomer, low-density polyethylene, organic multifunctional masterbatch, highly dispersed conductive functional filler, modified calcium sulfate whisker, grafted modified talc masterbatch, cross-linking agent, lubricant, and antioxidant are weighed, and then put into a high-speed mixer at a speed of 1500-2000r / min and a temperature of 30-50°C for mixing and stirring for 10-30min to prepare a mixture;
[0047] S2: The mixed material is put into a twin-screw blending extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw blending extruder is 165-195°C, the conveying section temperature is 160-190°C, the mixing section temperature is 180-205°C, the exhaust section temperature is 170-190°C, and the homogenization section temperature is 175-195°C. After the reactive melt blending is completed, the mixed material is extruded and granulated at 30-40°C water cooling to prepare a cross-linked antistatic supercritical microporous foaming material.
[0048] In a third aspect, the present invention provides an application of a cross-linked antistatic supercritical microporous foaming material in supercritical fluid microporous foaming sheets, injection molded parts, electronic packaging equipment, automotive parts and building materials.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] 1. The cross-linked antistatic supercritical microporous foaming material provided by the present invention and its preparation method and application are as follows: first, a self-developed organic multifunctional masterbatch is added to a HIPS matrix, wherein the ionic elements contained in the organic multifunctional masterbatch can promote the antistatic performance of the matrix, and can also optimize the arrangement of the molecular chains to form a denser conductive network inside the molecular chains; in addition, it can also be used as a compatibilizer between HIPS and low-density polyethylene (LDPE) to improve the phase interface of the matrix; at the same time, a highly dispersed conductive functional filler is introduced as the main antistatic component, and the highly dispersed conductive functional filler can effectively migrate in the polymer phase after surface activation, and form a synergistic enhancement effect with the organic multifunctional masterbatch to construct a multi-dimensional entangled conductive network, thereby enhancing the overall antistatic effect of the prepared cross-linked antistatic supercritical microporous foaming material; on this basis, a modified calcium sulfate whisker is introduced to regulate the melt strength of the matrix, and the modified calcium sulfate whisker can be effectively compounded in the molecular chain to form a higher molecular chain entanglement network to enhance the overall melt strength. In addition, a grafted modified talcum powder masterbatch is introduced, which is a talcum powder coated with a polymer molecular chain surface, has a surface tension similar to the matrix phase, can be uniformly and effectively embedded in the polymer phase, improves the interaction of the phase interface, and the surface grafted polymer molecular chain can effectively hinder the talcum powder from accumulating in the matrix, and can improve the overall toughness and strength of the material. Finally, a cross-linking agent is introduced, and a multiple cross-linked network of polymer-filler-polymer, polymer-polymer and filler-polymer is constructed in the matrix by melt reactive cross-linking, which not only contributes to the enhancement of the antistatic property of the matrix, but also improves the melt strength and basic mechanical properties of the material. Through the above formula and process, the multiple cross-linked network of the polymer is realized, the melt strength of the material is improved, and it is realized that there is good microporous foaming performance, excellent comprehensive mechanical properties, and stable antistatic performance, which is used for continuous extrusion supercritical fluid foaming production.
[0051] 2. In the present invention, the organic multifunctional masterbatch is a functional composite elastomer containing ionic units and having antistatic effects and volume-enhancing and toughening properties. The raw materials are maleic anhydride grafted styrene-ethylene-butadiene-styrene copolymer (SEBS-g-MAH), ionic liquid containing active groups, nano zinc oxide and erucic acid amide. By utilizing the principle of high-temperature ring-opening reaction, nano zinc oxide is added as a catalyst under melting conditions, and the catalytic ring-opening reaction of the active groups of the ionic liquid and maleic anhydride at high temperature is utilized to embed the ionic liquid containing active groups into the surface of SEBS-g-MAH to form a functional organic masterbatch with conductive ionic units. At the same time, high molecular weight erucic acid amide is added to the functional organic masterbatch to promote the movement of molecular chains and activate the arrangement of molecular chains, so as to obtain an organic multifunctional masterbatch with enhanced antistatic properties and toughened impact resistance.
[0052] 3. In the present invention, the conductive functional filler is activated and modified, and a coupling agent is used to activate the surface of the conductive functional filler to change the surface state of the conductive functional filler and improve the dispersion of the conductive functional filler in the matrix. Then, polyethylene wax with active groups, i.e. maleic anhydride grafted polyethylene wax, is added, which can not only improve the adhesion of the conductive filler to the polymer matrix, but also improve the heat resistance of the polymer, and promote the uniform dispersion of the conductive filler in the polymer matrix.
[0053] 4. The present invention first activates calcium sulfate whiskers with coupling agent II, and imparts highly active polar groups to the surfaces of the activated calcium sulfate whiskers. The activated calcium sulfate whiskers are then modified with an ionic liquid modifier, and a chemical reaction occurs between the active groups contained in the ionic liquid modifier and the active groups of the coupling agent II to form modified calcium sulfate whiskers having a conductive enhancement function and a material enhancement effect.
[0054] 5. The grafted modified talc masterbatch provided by the present invention adopts a unique filler modification method to graft polymer molecular chains to the surface of inorganic fillers to form a polymer-coated inorganic filler masterbatch, which helps to disperse the filler more evenly in the matrix and has better compatibility with the polymer matrix, and has the dual effects of reinforcement and toughening. First, a composite initiator crosslinking agent is prepared using a silane crosslinking agent containing an active group, an initiator, and styrene, and then high-impact polystyrene and activated ultrafine talc modified by a silane crosslinking agent containing an active group are subjected to high-temperature crosslinking modification. In this process, styrene is used as a crosslinking-promoting monomer and a peroxide initiator is used as a crosslinking initiator to graft high-impact polystyrene molecular chains to the surface of activated ultrafine talc, which can effectively improve the dispersion of activated ultrafine talc in the HIPS matrix, while improving the interfacial adhesion between the activated ultrafine talc and HIPS, improving the interfacial compatibility, and improving the overall mechanical properties of the material.
[0055] 6. The present invention utilizes LDPE as a cross-linked molecular chain and adds a cross-linking agent, which can form multiple cross-linked networks such as polymer-polymer, polymer-filler and polymer-filler-polymer in the matrix; on the one hand, it not only enhances the melt strength of the matrix, but also further improves the overall mechanical properties of the material through entanglement and cross-linking between the molecular chains; on the other hand, the multiple cross-linked structures are utilized to control the construction of the conductive network inside the molecular chain, thereby improving the overall conductivity of the material and obtaining an excellent antistatic functional material.
[0056] 7. The cross-linked antistatic supercritical microporous foam material provided by the present invention can be applied to various supercritical fluid microporous foamed sheets and injection molded parts of different forms. It can also be used in various electronic packaging equipment, automotive parts and building materials, and has broad application prospects. DETAILED DESCRIPTION
[0057] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] In the following examples, unless otherwise specified, all raw materials can be obtained from commercial sources.
[0059] Example 1
[0060] This embodiment provides a cross-linked antistatic supercritical microporous foam material, and its raw material formula is shown in Table 13 in terms of weight parts.
[0061] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the organic multifunctional masterbatch is shown in Table 1:
[0062] Table 1 Raw material formula of organic multifunctional masterbatch
[0063] Components Weight SEBS-g-MAH 90 Ionic liquids containing active groups 15 Nano zinc oxide 1 Erucic acid amide 2
[0064] In this embodiment, a method for preparing an organic multifunctional masterbatch is also provided, and the preparation method comprises the following steps:
[0065] According to the raw material formula of the organic multifunctional masterbatch in Table 1, SEBS-g-MAH, an ionic liquid containing an active group, nano zinc oxide and a high molecular weight erucic acid amide are weighed, mixed evenly, and then placed in a twin-screw extruder with a feeding section temperature of 145° C., a conveying section temperature of 150° C., a mixing section temperature of 165° C., a venting section temperature of 165° C., and a homogenizing section temperature of 170° C. for melt blending, extrusion and granulation to obtain an organic multifunctional masterbatch modified with high molecular weight erucic acid amide and activated with an ionic liquid containing an active group, and having enhanced antistatic properties and toughened impact resistance;
[0066] Among them, the ionic liquid containing active groups is one or more mixtures of 1-hydroxyethyl-3-methylimidazole perchlorate, trimethylhydroxyethylammonium chloride, 1-aminopropyl-3-methylimidazole hydrochloride or 1-aminopropyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt, with an active group content of 2% to 5% and a moisture content of <0.5%. Products of Shanghai Chengjie Chemical Co., Ltd. are preferred;
[0067] SEBS-g-MAH is preferably FG1901 GT from Kraton High Performance Polymers, USA;
[0068] High molecular weight erucamide was provided by Jiangxi Beier Hi-Tech New Materials Co., Ltd.
[0069] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foam material, the raw material formula of the highly dispersed conductive functional filler is shown in Table 2:
[0070] Table 2 Raw material formula of highly dispersed conductive functional filler
[0071] Components Weight Conductive functional filler 100 Coupling agent 1 5 Maleic anhydride grafted polyethylene wax 3
[0072] In this embodiment, a method for preparing a highly dispersed conductive functional filler is also provided, and the preparation method comprises the following steps:
[0073] According to the raw material formula of highly dispersed conductive functional filler in Table 2, conductive functional filler, coupling agent 1 and maleic anhydride grafted polyethylene wax were weighed, and a dry surface modification process was adopted. The weighed conductive functional filler and coupling agent 1 were first added to a high-speed mixer with an initial temperature of 60°C, kept at 60°C for 30 minutes, and then mixed and stirred at high speed for 1 hour to obtain a conductive functional filler activated and modified by the coupling agent, and then the weighed maleic anhydride grafted polyethylene wax was put into the high-speed mixer, and then the high-speed mixer was heated to 120°C, kept warm for 15 minutes, and then mixed and stirred for 45 minutes to obtain a highly dispersed conductive functional filler.
[0074] Wherein, the conductive functional filler is conductive carbon black, preferably M3710 produced by Jiangxi Black Cat Carbon Black Co., Ltd.;
[0075] The first coupling agent is a titanate coupling agent, preferably JTW-311 from Nanjing Jingtianwei Chemical Co., Ltd.;
[0076] The maleic anhydride grafted polyethylene wax is preferably AC 573P from Honeywell Company of the United States.
[0077] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foam material, the raw material formula of the modified calcium sulfate whisker is shown in Table 3:
[0078] Table 3 Raw material formula of modified calcium sulfate whisker
[0079] Components Weight Calcium sulfate whiskers 100 Coupling agent 2 1 Ionic Liquid Modifiers 0.6
[0080] In this embodiment, a method for preparing modified calcium sulfate whiskers is also provided, and the preparation method comprises the following steps:
[0081] According to the raw material formula of modified calcium sulfate whiskers in Table 3, calcium sulfate whiskers, coupling agent 2 and ionic liquid modifier were weighed, the weighed calcium sulfate whiskers and coupling agent 2 were placed in a high-speed mixer and stirred evenly, the temperature was raised to 60°C and kept warm for 30 minutes, and then mixed and stirred at high speed at 60°C for 1 hour to obtain calcium sulfate whiskers activated and modified by the coupling agent, and then the weighed ionic liquid modifier was added to the calcium sulfate whiskers activated and modified by the coupling agent, and high-speed mixing was continued at 60°C for 1.5 hours to obtain activated modified calcium sulfate whiskers modified with ionic liquid.
[0082] The calcium sulfate whiskers are anhydrous calcium sulfate whiskers, preferably XM-CSD300 produced by Guangdong Xinmei Nanotechnology Co., Ltd.
[0083] The second coupling agent is a silane coupling agent having an amino group, preferably KBE-903 provided by Shin-Etsu Chemical Co., Ltd. of Japan;
[0084] The ionic liquid modifier is an ionic liquid modifier containing a carboxyl group, preferably 1-carboxymethyl-3-methylimidazolium chloride produced by Shanghai Chengjie Chemical Co., Ltd.
[0085] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the grafted modified talc masterbatch is shown in Table 4:
[0086] Table 4 Raw material formula of grafted modified talc masterbatch
[0087] Components Weight Activated ultrafine talc 40 Silane crosslinker containing reactive groups 19 Initiator 0.1 Styrene 1 High Impact Polystyrene 60
[0088] In this embodiment, a method for preparing a grafted modified talc masterbatch is also provided, and the preparation method comprises the following steps:
[0089] S101: according to the formula of graft-modified talc masterbatch in Table 4, weigh activated ultrafine talc, silane crosslinking agent containing active groups, initiator, styrene, and high-impact polystyrene;
[0090] S102: adding the weighed silane crosslinking agent containing active groups, initiator, and styrene into a sealed container at room temperature and stirring for 30 minutes, and mixing them thoroughly to prepare a composite initiator crosslinking agent;
[0091] S103: adding the weighed high-impact polystyrene and activated ultrafine talc powder into a high-speed mixer, mixing them at a temperature of 50° C. and a rotation speed of 4000 r / min, and stopping the mixing until the surface of the high-impact polystyrene is softened and the activated ultrafine talc powder is evenly coated on the surface of the high-impact polystyrene, adding the mixed high-impact polystyrene and activated ultrafine talc powder into an internal mixer at a temperature of 185° C., mixing and internal mixing, and then extruding and granulating to prepare granulated particles;
[0092] S104: Add the granulated particles and the composite initiator cross-linking agent to a high-speed mixer, mix them thoroughly at room temperature and a rotation speed of 1500r / min to obtain a mixture, and add the mixture to a twin-screw extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw extruder is 175°C, the conveying section temperature is 190°C, the mixing section temperature is 210°C, the exhaust section temperature is 180°C, and the homogenization section temperature is 185°C. During the reactive blending process, the melt pressure also needs to be controlled to be maintained at 9MPa. After the reactive melt blending is completed, it is granulated by water cooling at 40°C to obtain a grafted modified talc masterbatch.
[0093] Among them, the activated ultrafine talc powder is preferably BHS-818AS produced by Quanzhou Xufeng Powder Raw Material Co., Ltd.;
[0094] The silane crosslinking agent containing an active group is a silane coupling agent having a vinyl group, preferably KBM-1003 produced by Shin-Etsu Chemical Co., Ltd. of Japan;
[0095] The initiator was bis(tert-butylperoxide isopropyl)benzene, provided by Liuyang Fangruida Chemical Co., Ltd.
[0096] Styrene purity ≥ 99%, preferably provided by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0097] The high impact polystyrene is a rubber copolymer modified polystyrene, preferably PH-55Y produced by Chi Mei Industrial Co., Ltd. of Taiwan, China.
[0098] This embodiment also provides a method for preparing a cross-linked antistatic supercritical microporous foam material, the preparation method comprising the following steps:
[0099] S1: According to the formula in Table 13, HIPS, thermoplastic elastomer, low-density polyethylene, organic multifunctional masterbatch, highly dispersed conductive functional filler, modified calcium sulfate whisker, grafted modified talc masterbatch, crosslinking agent, lubricant, and antioxidant were weighed, and then put into a high-speed mixer at a speed of 1800 r / min and a temperature of 50° C. for mixing and stirring for 15 minutes to prepare a mixture;
[0100] S2: The mixed material is fed into a twin-screw blending extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw blending extruder is 175°C, the conveying section temperature is 185°C, the mixing section temperature is 205°C, the exhaust section temperature is 190°C, and the homogenizing section temperature is 185°C. After the reactive melt blending is completed, the mixed material is extruded and granulated at 35°C water cooling to prepare a cross-linked antistatic supercritical microporous foam material.
[0101] Example 2
[0102] The raw materials and formula of this example are shown in Table 5, and its preparation process is the same as that of Example 1.
[0103] Example 3
[0104] The raw materials and formula of this example are shown in Table 5, and its preparation process is the same as that of Example 1.
[0105] Example 4
[0106] This embodiment provides a cross-linked antistatic supercritical microporous foam material, and its raw material formula is shown in Table 13 in terms of weight parts.
[0107] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the organic multifunctional masterbatch is shown in Table 5:
[0108] Table 5 Raw material formula of organic multifunctional masterbatch
[0109] Components Weight SEBS-g-MAH 60 Ionic liquids containing active groups 10 Nano zinc oxide 5 Erucic acid amide 5
[0110] In this embodiment, a method for preparing an organic multifunctional masterbatch is also provided, and the preparation method comprises the following steps:
[0111] According to the formula of the organic multifunctional masterbatch in Table 5, SEBS-g-MAH, an ionic liquid containing an active group, nano zinc oxide and a high molecular weight erucic acid amide are weighed, mixed evenly, and then placed in a twin-screw extruder with a feeding section temperature of 120° C., a conveying section temperature of 160° C., a mixing section temperature of 170° C., a venting section temperature of 155° C., and a homogenizing section temperature of 180° C. for melt blending, extrusion and granulation to obtain an organic multifunctional masterbatch modified with high molecular weight erucic acid amide and activated with an ionic liquid containing an active group, and having enhanced antistatic properties and toughened impact resistance;
[0112] Wherein, the ionic liquid containing active groups is one or more mixtures of 1-hydroxyethyl-3-methylimidazole perchlorate, trimethylhydroxyethylammonium chloride, 1-aminopropyl-3-methylimidazole hydrochloride or 1-aminopropyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt, with an active group content of 2% to 5% and a moisture content of <0.5%, preferably produced by Shanghai Chengjie Chemical Co., Ltd.;
[0113] SEBS-g-MAH is preferably FG1901 GT from Kraton High Performance Polymers, USA;
[0114] High molecular weight erucamide was provided by Jiangxi Beier Hi-Tech New Materials Co., Ltd.
[0115] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foam material, the raw material formula of the highly dispersed conductive functional filler is shown in Table 5:
[0116] Table 6 Raw material formula of highly dispersed conductive functional filler
[0117] Components Weight Conductive functional filler 80 Coupling agent 1 10 Maleic anhydride grafted polyethylene wax 1
[0118] In this embodiment, a method for preparing a highly dispersed conductive functional filler is also provided, and the preparation method comprises the following steps:
[0119] According to the raw material formula of highly dispersed conductive functional filler in Table 6, conductive functional filler, coupling agent 1 and maleic anhydride grafted polyethylene wax were weighed, and a dry surface modification process was adopted. The weighed conductive functional filler and coupling agent 1 were first added to a high-speed mixer with an initial temperature of 30°C, kept at 30°C for 15 minutes, and then mixed and stirred at high speed for 1.5 hours to obtain a conductive functional filler activated and modified by the coupling agent, and then the weighed maleic anhydride grafted polyethylene wax was put into the high-speed mixer, and then the high-speed mixer was heated to 100°C, kept warm for 30 minutes, and then mixed and stirred for 30 minutes to obtain a highly dispersed conductive functional filler.
[0120] Wherein, the conductive functional filler is conductive carbon black, preferably M3710 produced by Jiangxi Black Cat Carbon Black Co., Ltd.;
[0121] The first coupling agent is a titanate coupling agent, preferably JTW-311 from Nanjing Jingtianwei Chemical Co., Ltd.;
[0122] The maleic anhydride grafted polyethylene wax is preferably AC 573P from Honeywell Company of the United States.
[0123] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foam material, the raw material formula of the modified calcium sulfate whisker is shown in Table 7:
[0124] Table 7 Raw material formula of modified calcium sulfate whisker
[0125] Components Weight Calcium sulfate whiskers 90 Coupling agent 2 0.5 Ionic Liquid Modifiers 1
[0126] In this embodiment, a method for preparing modified calcium sulfate whiskers is also provided, and the preparation method comprises the following steps:
[0127] According to the raw material formula of the modified calcium sulfate whisker in Table 7, calcium sulfate whisker, coupling agent 2 and ionic liquid modifier are weighed, the weighed calcium sulfate whisker and coupling agent 2 are placed in a high-speed mixer and stirred evenly, the temperature is raised to 50°C and kept warm for 15 minutes, and then high-speed mixing and stirring are performed at 50°C for 1.5 hours to obtain calcium sulfate whiskers activated and modified by the coupling agent, and the weighed ionic liquid modifier is added to the calcium sulfate whiskers activated and modified by the coupling agent, and high-speed mixing is continued at 50°C for 1 hour to obtain activated modified calcium sulfate whiskers modified with ionic liquid.
[0128] The calcium sulfate whiskers are anhydrous calcium sulfate whiskers, preferably XM-CSD300 produced by Guangdong Xinmei Nanotechnology Co., Ltd.
[0129] The second coupling agent is a silane coupling agent having an amino group, preferably KBE-903 provided by Shin-Etsu Chemical Co., Ltd. of Japan;
[0130] The ionic liquid modifier is an ionic liquid modifier containing a carboxyl group, preferably 1-carboxymethyl-3-methylimidazolium chloride produced by Shanghai Chengjie Chemical Co., Ltd.
[0131] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the grafted modified talc masterbatch is shown in Table 8:
[0132] Table 8 Raw material formula of grafted modified talc masterbatch
[0133] Components Weight Activated ultrafine talc 50 Silane crosslinker containing reactive groups 5 Initiator 1 Styrene 2 High Impact Polystyrene 40
[0134] In this embodiment, a method for preparing a grafted modified talc masterbatch is also provided, and the preparation method comprises the following steps:
[0135] S101: according to the raw material formula of graft-modified talc masterbatch in Table 8, weigh activated ultrafine talc, silane crosslinking agent containing active groups, initiator, styrene, and high-impact polystyrene;
[0136] S102: adding the weighed silane crosslinking agent containing active groups, initiator, and styrene into a sealed container at room temperature and stirring for 15 minutes to fully mix them to prepare a composite initiator crosslinking agent;
[0137] S103: adding the weighed high-impact polystyrene and activated ultrafine talc powder into a high-speed mixer, mixing them at a temperature of 30° C. and a rotation speed of 3000 r / min, and stopping the mixing until the surface of the high-impact polystyrene is softened and the activated ultrafine talc powder is evenly coated on the surface of the high-impact polystyrene. Adding the mixed high-impact polystyrene and activated ultrafine talc powder into an internal mixer at a temperature of 190° C., mixing and internal mixing, and then extruding and granulating to prepare granulated particles;
[0138] S104: Add the granulated particles and the composite initiator cross-linking agent to a high-speed mixer, mix them thoroughly at room temperature and a rotation speed of 1000r / min to obtain a mixture, and add the mixture to a twin-screw extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw extruder is 140°C, the conveying section temperature is 150°C, the mixing section temperature is 180°C, the exhaust section temperature is 170°C, and the homogenization section temperature is 160°C. During the reactive blending process, the melt pressure also needs to be controlled to be maintained at 7MPa. After the reactive melt blending is completed, it is granulated by water cooling at 30°C to obtain a grafted modified talc masterbatch.
[0139] Among them, the activated ultrafine talc powder is preferably BHS-818AS produced by Quanzhou Xufeng Powder Raw Material Co., Ltd.;
[0140] The silane crosslinking agent containing an active group is a silane coupling agent having a vinyl group, preferably KBM-1003 produced by Shin-Etsu Chemical Co., Ltd. of Japan;
[0141] The initiator was bis(tert-butylperoxide isopropyl)benzene, provided by Liuyang Fangruida Chemical Co., Ltd.
[0142] Styrene purity ≥ 99%, preferably provided by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0143] The high impact polystyrene is a rubber copolymer modified polystyrene, preferably PH-55Y produced by Chi Mei Industrial Co., Ltd. of Taiwan, China.
[0144] This embodiment also provides a method for preparing a cross-linked antistatic supercritical microporous foam material, the preparation method comprising the following steps:
[0145] S1: According to the formula in Table 13, HIPS, thermoplastic elastomer, low-density polyethylene, organic multifunctional masterbatch, highly dispersed conductive functional filler, modified calcium sulfate whisker, grafted modified talc masterbatch, crosslinking agent, lubricant, and antioxidant were weighed, and then put into a high-speed mixer at a speed of 1500 r / min and a temperature of 30° C. for mixing and stirring for 30 minutes to prepare a mixture;
[0146] S2: The mixed material is fed into a twin-screw blending extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw blending extruder is 165°C, the conveying section temperature is 190°C, the mixing section temperature is 180°C, the exhaust section temperature is 170°C, and the homogenization section temperature is 175°C. After the reactive melt blending is completed, the mixed material is extruded and granulated at 30°C water cooling to prepare a cross-linked antistatic supercritical microporous foam material.
[0147] Example 5
[0148] This embodiment provides a cross-linked antistatic supercritical microporous foam material, and its raw material formula is shown in Table 13 in terms of weight parts.
[0149] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the organic multifunctional masterbatch is shown in Table 9:
[0150] Table 9 Raw material formula of organic multifunctional masterbatch
[0151]
[0152]
[0153] In this embodiment, a method for preparing an organic multifunctional masterbatch is also provided, and the preparation method comprises the following steps:
[0154] According to the raw material formula of the organic multifunctional masterbatch in Table 9, SEBS-g-MAH, an ionic liquid containing an active group, nano zinc oxide and a high molecular weight erucic acid amide were weighed, mixed evenly, and then placed in a twin-screw extruder with a feeding section temperature of 160° C., a conveying section temperature of 130° C., a mixing section temperature of 150° C., a venting section temperature of 150° C., and a homogenizing section temperature of 160° C. for melt blending, extrusion and granulation to obtain an organic multifunctional masterbatch modified with high molecular weight erucic acid amide and activated with an ionic liquid containing an active group, and having enhanced antistatic properties and toughened impact resistance;
[0155] Among them, the ionic liquid containing active groups is one or more mixtures of 1-hydroxyethyl-3-methylimidazole perchlorate, trimethylhydroxyethyl ammonium chloride containing hydroxyl or, 1-aminopropyl-3-methylimidazole hydrochloride or 1-aminopropyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt amino ionic liquid, with an active group content of 2% to 5% and a moisture content of <0.5%, preferably produced by Shanghai Chengjie Chemical Co., Ltd.;
[0156] SEBS-g-MAH preferably uses American Kraton FG1901 GT;
[0157] High molecular weight erucamide was provided by Jiangxi Beier Hi-Tech New Materials Co., Ltd.
[0158] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the highly dispersed conductive functional filler is shown in Table 10:
[0159] Table 10 Raw material formula of highly dispersed conductive functional filler
[0160] Components Weight Conductive functional filler 90 Coupling agent 1 7.5 Maleic anhydride grafted polyethylene wax 5
[0161] In this embodiment, a method for preparing a highly dispersed conductive functional filler is also provided, and the preparation method comprises the following steps:
[0162] According to the raw material formula of highly dispersed conductive functional filler in Table 10, conductive functional filler, coupling agent 1 and maleic anhydride grafted polyethylene wax were weighed, and a dry surface modification process was adopted. The weighed conductive functional filler and coupling agent 1 were first added to a high-speed mixer with an initial temperature of 45°C, kept at 45°C for 20 minutes, and then mixed and stirred at high speed for 1.2 hours to obtain a conductive functional filler activated and modified by the coupling agent, and then the weighed maleic anhydride grafted polyethylene wax was put into the high-speed mixer, and then the high-speed mixer was heated to 110°C, kept warm for 20 minutes, and then mixed and stirred for 40 minutes to obtain a highly dispersed conductive functional filler.
[0163] Wherein, the conductive functional filler is conductive carbon black, preferably M3710 produced by Jiangxi Black Cat Carbon Black Co., Ltd.;
[0164] The first coupling agent is a titanate coupling agent, preferably JTW-311 from Nanjing Jingtianwei Chemical Co., Ltd.;
[0165] The maleic anhydride grafted polyethylene wax is preferably AC 573P from Honeywell Company of the United States.
[0166] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the modified calcium sulfate whisker is shown in Table 11:
[0167] Table 11 Raw material formula of modified calcium sulfate whisker
[0168] Components Weight Calcium sulfate whiskers 95 Coupling agent 2 2 Ionic Liquid Modifiers 0.3
[0169] In this embodiment, a method for preparing modified calcium sulfate whiskers is also provided, and the preparation method comprises the following steps:
[0170] According to the raw material formula of the modified calcium sulfate whisker in Table 11, calcium sulfate whisker, coupling agent 2 and ionic liquid modifier are weighed, the weighed calcium sulfate whisker and coupling agent 2 are placed in a high-speed mixing and stirring machine and stirred evenly, the temperature is raised to 70°C and kept warm for 20 minutes, and then high-speed mixing and stirring are performed at 70°C for 1.2 hours to obtain calcium sulfate whiskers activated and modified by the coupling agent, and the weighed ionic liquid modifier is added to the calcium sulfate whiskers activated and modified by the coupling agent, and high-speed mixing is continued at 70°C for 2 hours to obtain activated modified calcium sulfate whiskers modified with ionic liquid.
[0171] The calcium sulfate whiskers are anhydrous calcium sulfate whiskers, preferably XM-CSD300 produced by Guangdong Xinmei Nanotechnology Co., Ltd.
[0172] The second coupling agent is a silane coupling agent having an amino group, preferably KBE-903 provided by Shin-Etsu Chemical Co., Ltd. of Japan;
[0173] The ionic liquid modifier is an ionic liquid modifier containing a carboxyl group, preferably 1-carboxymethyl-3-methylimidazolium chloride produced by Shanghai Chengjie Chemical Co., Ltd.
[0174] Among them, in the raw material formula of the cross-linked antistatic supercritical microporous foaming material, the raw material formula of the grafted modified talc masterbatch is shown in Table 12:
[0175] Table 12 Raw material formula of grafted modified talc masterbatch
[0176]
[0177]
[0178] In this embodiment, a method for preparing a grafted modified talc masterbatch is also provided, and the preparation method comprises the following steps:
[0179] S101: according to the raw material formula of graft-modified talc masterbatch in Table 12, weigh activated ultrafine talc, silane crosslinking agent containing active groups, initiator, styrene, and high-impact polystyrene;
[0180] S102: adding the weighed silane crosslinking agent containing active groups, initiator, and styrene into a sealed container at room temperature and stirring for 20 minutes, and mixing them thoroughly to prepare a composite initiator crosslinking agent;
[0181] S103: adding the weighed high-impact polystyrene and activated ultrafine talc powder into a high-speed mixer, mixing them at a temperature of 40° C. and a rotation speed of 3500 r / min, and stopping the mixing until the surface of the high-impact polystyrene is softened and the activated ultrafine talc powder is evenly coated on the surface of the high-impact polystyrene, adding the mixed high-impact polystyrene and activated ultrafine talc powder into an internal mixer at a temperature of 150° C., mixing and internal mixing, and then extruding and granulating to prepare granulated particles;
[0182] S104: Add the granulated particles and the composite initiator cross-linking agent to a high-speed mixer, mix them thoroughly at room temperature and a rotation speed of 2000r / min to obtain a mixture, and add the mixture to a twin-screw extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw extruder is 180°C, the conveying section temperature is 180°C, the mixing section temperature is 220°C, the exhaust section temperature is 195°C, and the homogenization section temperature is 190°C. During the reactive blending process, the melt pressure also needs to be controlled to be maintained at 10MPa. After the reactive melt blending is completed, it is granulated by water cooling at 50°C to obtain a grafted modified talc masterbatch.
[0183] Among them, the activated ultrafine talc powder is preferably BHS-818AS produced by Quanzhou Xufeng Powder Raw Material Co., Ltd.;
[0184] The silane crosslinking agent containing an active group is a silane coupling agent having a vinyl group, preferably KBM-1003 produced by Shin-Etsu Chemical Co., Ltd. of Japan;
[0185] The initiator was bis(tert-butylperoxide isopropyl)benzene, provided by Liuyang Fangruida Chemical Co., Ltd.
[0186] Styrene purity ≥ 99%, preferably provided by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0187] The high impact polystyrene is a rubber copolymer modified polystyrene, preferably PH-55Y produced by Chi Mei Industrial Co., Ltd. of Taiwan, China.
[0188] This embodiment also provides a method for preparing a cross-linked antistatic supercritical microporous foam material, the preparation method comprising the following steps:
[0189] S1: According to the formula in Table 13, HIPS, thermoplastic elastomer, low-density polyethylene, organic multifunctional masterbatch, highly dispersed conductive functional filler, modified calcium sulfate whisker, grafted modified talc masterbatch, crosslinking agent, lubricant, and antioxidant were weighed, and then put into a high-speed mixer at a speed of 2000 r / min and a temperature of 40° C. for mixing and stirring for 20 minutes to prepare a mixture;
[0190] S2: The mixed material is fed into a twin-screw blending extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw blending extruder is 195°C, the conveying section temperature is 160°C, the mixing section temperature is 190°C, the exhaust section temperature is 180°C, and the homogenizing section temperature is 195°C. After the reactive melt blending is completed, the mixed material is extruded and granulated at 40°C water cooling to prepare a cross-linked antistatic supercritical microporous foam material.
[0191] Example 6
[0192] The raw materials and formula of this example are shown in Table 13, and the preparation process is the same as that of Example 1.
[0193] Comparative Example 1
[0194] The raw materials and formula of this comparative example are shown in Table 13, and its preparation process is the same as that of Example 1.
[0195] Comparative Example 2
[0196] The raw materials and formula of this comparative example are shown in Table 13, and its preparation process is the same as that of Example 1.
[0197] Comparative Example 3
[0198] The raw materials and formula of this comparative example are shown in Table 13, and its preparation process is the same as that of Example 1.
[0199] Comparative Example 4
[0200] The raw materials and formula of this comparative example are shown in Table 13, and its preparation process is the same as that of Example 1.
[0201] Comparative Example 5
[0202] The raw materials and formula of this comparative example are shown in Table 13, and its preparation process is the same as that of Example 1.
[0203] Table 13
[0204]
[0205]
[0206] Experimental example
[0207] The performance tests were carried out on the cross-linked antistatic supercritical microporous foam materials prepared in Examples 1-6 and Comparative Examples 1-5. The test results are shown in Table 14.
[0208] Table 14
[0209]
[0210]
[0211] It can be seen from the data in Table 14 that, compared with Example 2, Comparative Example 1 uses traditional unmodified conductive carbon black, which is easy to agglomerate in the system, resulting in unstable conductivity of the system. At the same time, the agglomerated carbon black has poor compatibility with the polymer phase, resulting in decreased mechanical properties of the system; Compared with Example 2, Comparative Example 2 adds highly dispersed conductive functional fillers, but does not add organic functional masterbatch, the antistatic effect of the material decreases, and the overall mechanical properties of the material decrease; Compared with Example 2, Comparative Example 3 does not add modified calcium sulfate whiskers, and the strength and hardness of the material itself decrease. And the melt strength is also reduced to a certain extent; compared with Example 2, Comparative Example 4 introduces ordinary talcum powder masterbatch, which does not have a high surface affinity, has a weak interaction with the polymer matrix, and also has the problem of uneven dispersion in the matrix, resulting in a decrease in the overall mechanical properties of the material; compared with Example 2, Comparative Example 5 removes the cross-linking agent, the uncross-linked molecular chain has a larger fluidity, and the interaction between the molecular chains is weak, resulting in a decrease in the melt strength of the material, affecting the mechanical properties of the material, and is not conducive to the supercritical microporous foaming of the HIPS material.
[0212] The addition of organic multifunctional masterbatch containing ionic elements can not only promote the movement of molecular chains, activate the arrangement of molecular chains, improve the plasticizing ability of materials, improve the interfacial adhesion of materials, and enhance the strength of materials, but also utilize the migration of ionic elements within the system to form a weak conductive network structure to enhance the antistatic property of the system. The introduced highly dispersed conductive functional filler migrates evenly in the phase interface of the HIPS system to form a stable conductive network structure, and synergistically enhances the conductive properties of the system with the organic multifunctional masterbatch, providing HIPS with more excellent antistatic properties. At the same time, the introduced calcium sulfate whiskers modified with ionic elements can not only serve as nucleating agents for supercritical microporous foaming, but also enhance the hardness of the material, improve the strength of the material, promote the entanglement of molecular chains, and reduce the fluidity of molecular chains. The introduced grafted modified talc masterbatch has high compatibility with the polymer matrix, can effectively improve the dispersion of talc in the HIPS matrix, and at the same time improve the interfacial adhesion between talc and HIPS, improve the interfacial compatibility, improve the overall mechanical properties of the material, and make up for the lack of toughness of the material caused by the introduction of conductive fillers and cross-linking. In addition, the introduced cross-linking agent can build a complete multiple cross-linking network with LDPE and SBS, etc., forming a polymer-polymer, polymer-filler and polymer-filler-polymer multiple cross-linking network in the system, improving the melt strength of the material, enhancing the comprehensive mechanical properties of the material, forming a more stable antistatic effect, and at the same time, a better cross-linking network is more conducive to the supercritical microporous foaming of HIPS.
[0213] The invention adopts cross-linking modification technology to construct multiple cross-linking networks between organic masterbatch, inorganic filler and polymer matrix, so that the conductive filler dispersed in the polymer phase has a stable phase structure and can form a stable conductive network, so that the material has a more excellent antistatic effect. At the same time, the organic functional masterbatch containing ionic elements and the modified calcium sulfate whisker introduced can promote the formation of the conductive network and enhance the conductive effect of the polymer matrix; and the talcum powder modified by polymer grafting is introduced as a toughening and reinforcing modified filler to improve the comprehensive mechanical properties of the material; finally, the HIPS material which has both excellent antistatic effect and excellent comprehensive mechanical properties and can be used for supercritical microporous foaming is obtained.
[0214] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0215] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A cross-linked antistatic supercritical microporous foam material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of HIPS, 10-15 parts of thermoplastic elastomer, 5-10 parts of low-density polyethylene, 10-15 parts of organic multifunctional masterbatch, 5-10 parts of highly dispersed conductive functional filler, 5-10 parts of modified calcium sulfate whisker, 5-10 parts of grafted modified talc masterbatch, 1-5 parts of crosslinking agent, 1-5 parts of lubricant and 1-5 parts of antioxidant; The organic multifunctional masterbatch comprises the following raw materials in parts by weight: 60-90 parts of SEBS-g-MAH, 10-20 parts of ionic liquid containing active groups, 1-5 parts of nano zinc oxide, and 1-5 parts of erucic acid amide; The highly dispersed conductive functional filler comprises the following raw materials in parts by weight: 80-100 parts of conductive functional filler, 5-10 parts of coupling agent, and 1-5 parts of maleic anhydride grafted polyethylene wax; The modified calcium sulfate whisker comprises the following raw materials in parts by weight: 90-100 parts of calcium sulfate whisker, 0.5-2 parts of coupling agent II, and 0.3-1 parts of ionic liquid modifier; The grafted modified talc masterbatch comprises the following raw materials in parts by weight: 40-50 parts of activated ultrafine talc, 5-20 parts of a silane crosslinking agent containing an active group, 0.1-1 parts of an initiator, 1-2 parts of styrene, and 40-60 parts of high-impact polystyrene.
2. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The preparation method of the organic multifunctional masterbatch comprises the following steps: According to the raw material formula of organic multifunctional masterbatch, SEBS-g-MAH, ionic liquid containing active groups, nano zinc oxide and erucic acid amide are weighed, and the weighed SEBS-g-MAH, ionic liquid containing active groups, nano zinc oxide and erucic acid amide are fully mixed by reactive melt blending method, and placed in a twin-screw extruder for melt blending, extrusion and granulation. During the melt blending, extrusion and granulation, the feeding section temperature of the twin-screw extruder is 120°C-160°C, the conveying section temperature is 130°C-160°C, the mixing section temperature is 150°C-170°C, the exhaust section temperature is 150°C-165°C, and the homogenization section temperature is 160°C-180°C. After the melt blending, extrusion and granulation are completed, the organic multifunctional masterbatch is obtained.
3. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The ionic liquid containing active groups is any one or more of ionic liquid containing sulfonic acid groups, ionic liquid containing vinyl groups, ionic liquid containing carboxyl groups, ionic liquid containing hydroxyl groups, ionic liquid containing amino groups or ionic liquid containing epoxy groups, mixed in any proportion.
4. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The preparation method of the highly dispersed conductive functional filler comprises the following steps: According to the raw material formula of highly dispersed conductive functional filler, conductive functional filler, coupling agent 1 and maleic anhydride grafted polyethylene wax are weighed, and a dry surface modification process is adopted. The weighed conductive functional filler and coupling agent 1 are first added to a high-speed mixer with an initial temperature of 30-60°C, and kept at 30-60°C for 15-30 minutes, and then mixed and stirred at a high speed for 1-1.5 hours to obtain a conductive functional filler activated and modified by the coupling agent, and then the weighed maleic anhydride grafted polyethylene wax is put into the high-speed mixer, and then the high-speed mixer is heated to 100-120°C, kept warm for 15-30 minutes, and then mixed and stirred for 30-45 minutes to obtain a highly dispersed conductive functional filler.
5. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The conductive functional filler is any one or more of conductive carbon black, multi-walled carbon nanotubes, graphene, carbon fiber powder, silver metal powder, copper metal powder, and nickel metal powder mixed in any proportion; The coupling agent 1 and the coupling agent 2 are independently selected from any one or more of silane coupling agents, titanate coupling agents, and aluminate coupling agents and mixed in any proportion; The ionic liquid modifier is any one or more of a carboxyl-containing ionic liquid, a hydroxyl-containing ionic liquid, an amino-containing ionic liquid, a vinyl-containing ionic liquid, an ester-containing ionic liquid, and an ether-containing ionic liquid, mixed in any proportion.
6. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The preparation method of the modified calcium sulfate whisker comprises the following steps: According to the raw material formula of modified calcium sulfate whiskers, calcium sulfate whiskers, coupling agent II and ionic liquid modifier are weighed, the weighed calcium sulfate whiskers and coupling agent II are placed in a high-speed mixer and stirred evenly, the temperature is raised to 50-70°C and kept warm for 15-30 minutes, and then high-speed mixing and stirring are performed at 50-70°C for 1-1.5 hours to obtain calcium sulfate whiskers activated and modified by the coupling agent, and the weighed ionic liquid modifier is added to the calcium sulfate whiskers activated and modified by the coupling agent, and high-speed mixing is continued at 50-70°C for 1-2 hours to obtain activated modified calcium sulfate whiskers modified with ionic liquid.
7. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The preparation method of the grafted modified talc masterbatch comprises the following steps: S101: according to the formula, weigh activated ultrafine talc powder, silane crosslinking agent containing active groups, initiator, styrene, and high impact polystyrene; S102: adding the weighed silane crosslinking agent containing active groups, initiator, and styrene into a sealed container at room temperature and stirring for 15-30 minutes, and mixing them thoroughly to prepare a composite initiator crosslinking agent; S103: adding the weighed high-impact polystyrene and activated ultrafine talc powder into a high-speed mixer, mixing them at a temperature of 30-50° C. and a rotation speed of 3000-4000 r / min, and stopping the mixing until the surface of the high-impact polystyrene is softened and the activated ultrafine talc powder is evenly coated on the surface of the high-impact polystyrene, adding the mixed high-impact polystyrene and activated ultrafine talc powder into an internal mixer at a temperature of 150-190° C., mixing and internal mixing, and then extruding and granulating to prepare granulated particles; S104: adding the granulated particles and the composite initiator crosslinking agent to a high-speed mixer, fully mixing them at room temperature and a rotation speed of 1000-2000r / min to obtain a mixture, and adding the mixture to a twin-screw extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw extruder is 140-180°C, the conveying section temperature is 150-190°C, the mixing section temperature is 180-220°C, the exhaust section temperature is 170-195°C, and the homogenization section temperature is 160-190°C. During the reactive blending process, the melt pressure needs to be controlled to be maintained at 7-10MPa. After the reactive melt blending is completed, the mixture is granulated by water cooling at 30-50°C to obtain a grafted modified talc masterbatch.
8. The cross-linked antistatic supercritical microporous foam material according to claim 1, characterized in that: The active group in the active group-containing silane crosslinking agent is any one or more of vinyl, carboxyl, hydroxyl, epoxy, and amino groups mixed in any proportion; The initiator is a peroxide initiator.
9. A method for preparing the cross-linked antistatic supercritical microporous foam material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: According to the formula of the cross-linked antistatic supercritical microporous foaming material, HIPS, thermoplastic elastomer, low-density polyethylene, organic multifunctional masterbatch, highly dispersed conductive functional filler, modified calcium sulfate whisker, grafted modified talc masterbatch, cross-linking agent, lubricant, and antioxidant are weighed, and then put into a high-speed mixer at a speed of 1500-2000r / min and a temperature of 30-50°C for mixing and stirring for 10-30min to prepare a mixture; S2: The mixed material is put into a twin-screw blending extruder for reactive melt blending. During the reactive melt blending process, the feeding section temperature of the twin-screw blending extruder is 165-195°C, the conveying section temperature is 160-190°C, the mixing section temperature is 180-205°C, the exhaust section temperature is 170-190°C, and the homogenization section temperature is 175-195°C. After the reactive melt blending is completed, the mixed material is extruded and granulated at 30-40°C water cooling to prepare a cross-linked antistatic supercritical microporous foaming material.
10. Use of the cross-linked antistatic supercritical microporous foam material according to any one of claims 1 to 8 in supercritical fluid microporous foamed sheets, injection molded parts, electronic packaging equipment, automotive parts and building materials.
Citation Information
Patent Citations
A microporous foamed HIPS electromagnetic shielding material, its preparation method and application
CN111961305B
A supercritical microporous TPE foam and its preparation method
CN113444363B
Antistatic HIPS material and preparation method thereof
CN115058044A
Cited By
Preparation process of rigid foam polyurethane insulation board
CN120645362A
Low-density anti-aging HIPS (High Impact Polystyrene) material as well as preparation method and application thereof
CN120648146A